Ophthalmology-focused publications and findings on COVID-19: A systematic review. Issue 4 (July 2021) - Jin, Ya-Ping; Trope, Graham E; El-Defrawy, Sherif; Liu, Elin Y; Buys, Yvonne M
Purpose: To summarize COVID-19 research endeavors by ophthalmologists/researchers in terms of publication numbers, journals and author countries, and to detail key findings. Methods: The LitCovid database was systematically reviewed for ophthalmology-focused COVID-19 articles. The quality of the evidence was assessed for articles investigating conjunctivitis in COVID-19 patients. Results: There were 21, 364 articles in LitCovid on June 12, 2020, of which 215 (1%) were ophthalmology-focused. Of articles on COVID-19 transmission, 3.3% were ophthalmology-focused. Ophthalmology-focused articles were published in 68 journals and originated from 25 countries. The top five countries publishing ophthalmology-focused articles (China, India, United States of America, Italy, and United Kingdom) produced 145/215 (67%) articles. A total of 16 case reports/series from eight countries reported that conjunctivitis can be the initial or the only symptom of COVID-19 infection. Conjunctivitis may occur in the middle phase of COVID-19 illness. A total of 10 hospital-based cross-sectional studies reported that between 0% and 31.6% of COVID-19 patients have conjunctivitis or other ocular conditions, with a pooled prevalence of 5.5% reported in a meta-analysis. Viral RNA was detected in conjunctival swabs of patients with and without ocular manifestations, after resolution of conjunctivitis, after nasopharyngeal swabs turned negative and in retina of deceased COVID-19 patients. Conclusion: Within 3 months of declaring the COVID-19 pandemic, 215 ophthalmology-focused articles were published in PubMed, concentrating on disease manifestations and transmission. The reported presence of conjunctivitis or other ocular conditions in COVID-19 patients is varied. Clinicians should be alert for ocular involvement in COVID-19 infections and possible ocular transmission even in patients without ocular symptoms.